Parkin and PINK1 mutations in early-onset Parkinson's disease: comprehensive screening in publicly available cases and control. Issue 6 (6th April 2009) - Brooks, J; Ding, J; Simon-Sanchez, J; Paisan-Ruiz, C; Singleton, A B; Scholz, S W
Abstract : Background: Mutations in parkin and PTEN-induced protein kinase ( PINK1 ) represent the two most common causes of autosomal recessive parkinsonism. The possibility that heterozygous mutations in these genes also predispose to disease or lower the age of disease onset has been suggested, but currently there is insufficient data to verify this hypothesis conclusively. Objective: To study the frequency and spectrum of parkin and PINK1 gene mutations and to investigate the role of heterozygous mutations as a risk factor for early-onset Parkinson's disease (PD). Methods: All exons and exon–intron boundaries of PINK1 and parkin were sequenced in 250 patients with early-onset PD and 276 normal controls. Gene dosage measurements were also performed, using high-density single-nucleotide polymorphism arrays. Results: In total 41 variants were found, of which 8 have not been previously described ( parkin : p.A38VfsX6, p.C166Y, p.Q171X, p.D243N, p.M458L; PINK1 : p.P52L, p.T420T, p.A427E). 1.60% of patients were homozygous or compound heterozygous for pathogenic mutations. Heterozygosity for pathogenic parkin or PINK1 mutations was over-represented in patients compared with healthy controls (4.00% vs. 1.81%) but the difference was not significant (p = 0.13). The mean age at disease onset was significantly lower in patients with homozygous or compound heterozygous mutations than in patients with heterozygous mutations (mean difference 11 years, 95% CI 1.4 to 20.6, p = 0.03). There was no significant difference in the mean age at disease onset in heterozygous patients compared with patients without a mutation in parkin or PINK1 (mean difference 2 years, 95% CI −3.7 to 7.0, p = 0.54). Conclusions: Our data support a trend towards a higher frequency of heterozygosity for pathogenic parkin or PINK1 mutations in patients compared with normal controls, but this effect was small and did not reach significance in our cohort of 250 cases and 276 controls.